Imaging Negative Parathyroid Adenoma - Kader, Md Abdul; Azad, Md Abdul Kalam; Rahaman, Md Ferdous Ur; Khan, Abed Hussain; Chowdhury, MA Jalil; Aziz, Md Mohibul; Karim, Enayet (Journal of Medicine, 2010)
Primary hyperparathyroidism typically presents with skeletal and renal manifestations. In most (80-85%) cases, the cause is a single parathyroid adenoma. We present a case of 36-year-old lady of primary hyperparathyroidism presented with multiple fractures, nephrolithiasis, and nephrocalcinosis. All of the imaging techniques to localize the cause were negative. She underwent surgical neck exploration with detection of left parathyroid adenoma. Her post-operative period was uneventful with significant clinical and biochemical improvement. Keywords: Primary hyperparathyroidism, hyperparathyroidism, hypercalcemia, parathyroid imaging. DOI:10.3329/jom.v11i1.4281 J Medicine 2010: 11: 83-85